Acrobat Ant, Crematogaster ashmeadi Emery (Insecta: Hymenoptera: Formicidae: Myrmicinae) - Emily V. Saarinen (EDIS)
The ant Crematogaster ashmeadi (Emery) is commonly known as an acrobat ant. There are perhaps 10 species of Crematogaster in Florida, and C. ashmeadi is commonly found throughout the state (Deyrup, personal communication). Members of this genus are referred to as acrobat ants because of the flexible way that a worker holds its abdomen (gaster) up over the rest of its body. This document is EENY-333 , one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: August 2004.